Rethinking Conservation and Restoration Strategies of Endangered and Key Medicinal Clavicarpa Plants in Yunnan‐Kweichow Plateau's Karst Areas Under Climate Change - Chao Luo; Baiyang He; Yulu Wu; Yuteng Xue; Huang Deng; Shanman Li; Xianghong Dong; Litang Lu (Ecology and Evolution)
ABSTRACT The Clavicarpa species, valued for their pharmaceutical, ornamental, and economic importance, exhibit notable rarity and endemism in the Karst areas of the Yunnan‐Kweichow Plateau in China. These species face significant threats from habitat loss and fragmentation, leading to a decline in biodiversity. To mitigate these threats, the Maxent algorithm was employed to analyze current and future distribution patterns, with a particular focus on the influence of climate variables in predicting potential distribution shifts and assessing extinction risks under the optimistic SSP1‐2.6 and the pessimistic SSP5‐8.5 socioeconomic scenarios. The EC‐Earth3‐Veg, MRI‐ESM2‐0, and MPI‐ESM1‐2‐HR models were utilized for conservation status assessment and project future distributions for four time periods: the present, 2030s, 2050s, and 2070s. The minimum temperature during the coldest month (Bio 6) was identified as the most critical environmental factor, influencing both habitat contraction and expansion. Our modeling indicates that regions such as South, Central, and East China, particularly areas east of the Aihui‐Tengchong line and south of the Yangtze River, exhibit the highest suitability for Clavicarpa species within the geographical coordinates of 18° N–45° N and 97° E–120° E. Conversely, climate change projections suggest a habitat expansion for Impatiens claviger, Impatiens tubulosa, Impatiens pritzelii, and Impatiens apalophylla, while Impatiens guizhouensis and Impatiens wilsonii face increased extinction risks. Specifically, I. claviger, I. tubulosa, and I. apalophylla are expected to shift northward, necessitating potential relocation to southern regions, while I. guizhouensis and I. wilsonii are projected to experience habitat losses of over 23.94% and 9.13%, respectively. Our research provides a robust scientific foundation for the conservation and sustainable utilization of these important pharmaceutical species and offers a framework for effective biodiversity management. We recommend using protected areas as a basis for the future conservation, breeding, cultivation, and utilization of Clavicarpa species.